Staying Apart but Staying Together: Establishing Learners' Community in Remote Teaching - Hamid Ali Khan Eusafzai (Universitas Muhammadiyah Prof. DR. HAMKA, 2020)
The cliché “Learning is a social act” highlights the critical role of social interaction in the process of learning. However, in the wake of COVID-19 forced campus closures and the resultant remote teaching minimizes the opportunities for such interactions mainly because teachers and students are forced to stay in isolation in their homes and come together for a limited time on the computer screen only. To overcome this limitation, teaching and assessment interventions are needed to build a sense of community (SoC) and therefore optimize students learning. This paper focuses on one such intervention and its perceived benefits for students learning of the course contents in the context of an English for academic purposes course delivered at an international university campus in Tajikistan. The paper shares how conditions were created to build a SoC among the students and how it was beneficial for them. The paper has implications for practitioners as it shares a practical example of using social interaction for enhanced learning in an online environment and therefore may stimulate some further ideas for using community building for the enhanced achievement of the learning outcomes.